Generalized double binomial sums families by generating functions - Kiliç, Emrah; Belbachir, Hacène (Utilitas Mathematica, 2017)
We consider various double binomial sums related with certain second, third and fourth order recursions. Moreover a new binomial sums with complex coefficients related with a generalized second order recursion is derived. The generating function methods are used to prove them. Also some interesting examples are given.